PARTISIPASI POLITIK GENERASI Z PADA NEW MEDIA MENJELANG PEMILIHAN GUBERNUR SULAWESI TENGGARA 2024 - Indra Lestari; Iriyani Astuti Arief; Muh.Djufri Rachim (Journal Publicuho, 2024)
The purpose of this research is to identify and eximine Participation of Generation Z in New Media ahead of the Southeast Sulawesi gubernatorial election in 2024. The research method used is mix methods, which combine qualitative and quantitative research methodologies. With data collection techniques using questionnaires distributed via google form, interview, literature study, and documentation. The three steps of the analysis technique are data reduction, data display, and conclusion drawing. According to the research indicate that New media plays a central role in shaping Generation Z's understanding, attitudes and political engagement. Generation Z, as a technology-savvy group, utilizes new media not only as a source of information, but also as a tool to express political identity. They think that the political content they see through new media, especially social media, tends to be easier to understand compared to other news sources. The most frequently accessed political content on social media is political memes and humor, debates and political educational content. The research results also show that Generation Z's political opinions are largely formed through what they see on social media. Candidates for Governor who are more active on social media have the greatest chance of winning the votes of Generation Z, because most of them also know the Candidate for Governor of Southeast Sulawesi through social media.